Structural and spectroscopic investigation on antioxidant dipeptide, L-Methionyl-L-Serine: A combined experimental and DFT study - Kecel Gündüz, Serda; Bıçak, Bilge; Çelik, Sefa; Özel, Ayşen E.; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2017)
The focus of this study is to determine the conformational, structural and vibrational properties of Methionyl-Serine dipeptide (L-Methionyl-L-Serine, Met-Ser), a biological active molecule. To investigate their energetically preferred conformations, molecular mechanics methods were utilized to determine the optimal conformations of the 3402 different dihedral angle values of the backbone and side chains. It was found that the extended (e) backbone shape in the LB conformational range was the most stable LMethionyl-L-Serine dipeptide conformation, with 3.12 kcal/mol of energy. Density Functional Theory (DFT) was used to determine the optimized geometry, the vibrational wavenumbers and modes of the title dipeptide values, with 6-31G (d,p) and 6-311++G (d,p) basis sets. The potential energy distribution data was used to carry out the assignment of the bands. In addition, the vibrational spectra of the most stable conformer and its dimer form were determined and the obtained results were compared with the experimental IR and Raman spectra in the solid phase. To determine the presence of intramolecular charge transfer, molecular dipole moment, polarizability and hyperpolarizability, the Natural Bond Orbital (NBO), HOMO LUMO calculations, the linear polarizability (alpha) and the first order hyperpolarizability (fio) value analyses of the investigated molecule were carried out using the DFT with the B3LYP/6-31++G(d,p) basis set. This study aims to determine a relatively stable conformation of antioxidant dipeptide and to investigate the molecular geometry, molecular vibrations and hydrogen bonding interactions between monomeric and dimeric forms of Methiony-Serine dipeptide. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Methionyl-Serine dipeptide; Antioxidant; Methionine; DFT; Solid-State; Amino-Acid; Theoretical-Analysis; Raman-Spectra; Ft-Raman; Ir; Hardness; Cancer; Polarizability; Nitroaniline